Metabolic conversion as a pre-receptor control mechanism for lipophilic hormones. - Nobel, S; Abrahmsen, L; Oppermann, U (2001)
The majority of physiological effects mediated by steroids, retinoids and thyroids is accomplished by binding to members of the nuclear receptor superfamily of ligand activated transcription factors. The complex specific effects of lipid hormones depend not only on receptor expression, distribution and interactions, but also on the availability and metabolic conversion of the hormone itself. The cell-specific metabolic activation of inactive hormone precursors introduces a further level of hormonal regulation, and constitutes an important concept in endocrinology. The metabolic reactions carried out are achieved by dehydrogenases/reductases, hydroxylases and other enzymes, acting on ligands of the steroid/thyroid/retinoic hormone receptor superfamily. The concept implies that these tissue- and cell-specific metabolic conversions contribute to lipid hormone action, thus pointing to novel targets in drug development. All components of this signalling system, the hormone compounds, the receptor proteins, and modifying enzyme families originate from an early metazoan date, emphasizing the essential nature of all elements for development and diversification of vertebrate life.